The anisotropic structure of electro conductive leather studied by Van der Pauw method - Shabani, Aulon (Array, 2019)
Determining the surface resistance of electro conductive refined natural leather materials is in the focus of this paper. Natural leather samples are initially transformed to conductive by applying chemical treatment process known as polymerization. Due to the existence of various techniques for measuring electrical resistance of conductive materials, we are focused on measuring surface resistance by arranging four electrodes in the edges of square leather samples, also known as Van der Pauw method. Improving the results accuracy, we use a multi-variant electrode placement over the sample edges. The result is the average of all results gained for different placements. Moreover, we use this electrode placement technique to analyse the anisotropy of conductive samples. The results of this research provide important knowledge about leather chemical treatment and its electrical proprieties.